(untitled) (REMUNOM, 2023)
ABSTRACT The general objective of this work is to study the pathological manifestations in mortar coverings in buildings due to poor execution. Specifically, highlighting the main pathological manifestations arising, elucidating preventive and corrective measures to avoid such symptoms in mortared coverings and the financial impact of corrections in mortared coverings. In this line of reasoning, this study is a literature review with data collection carried out through an electronic search in the Google Scholar, Periódicos Capes, SciELO and the Brazilian Digital Library of Theses and Dissertations (BDTD) databases. Thus, after collecting data, it can be observed that the main causes of pathological manifestations in coatings occur during the execution stages, followed by the poor quality of the materials used and the lack of maintenance. The facade project, in most cases, does not yet exist, especially in small projects, and when it does exist, details are missing. The façade project should be mainly an executive project to reduce the possibility of pathological manifestations. In this sense, investing in facade projects, qualified/specialized labor and periodic maintenance are the relationships that have the capacity to optimize the performance of facades and avoid high costs with future restorations. Keywords: Pathological manifestations. Mortar. Buildings.